Evaluation of the Drug Receiving and Storage System at Pharmacy X in Bandung City Based on Technical Instructions for PharmaceuticalService Standards at Pharmacies - Ade Rezki Ilahi; Yoppi Iskandar (Fakultas Farmasi Institut Kesehatan Medistra Lubuk Pakam, 2025)
Background: Discrepancies in the quantity of drugs received, damaged packaging, and improper storage that fails to consider drug stability are some of the common issues encountered. Objective: This study aims to evaluate the drug receiving and storage systems at Pharmacy X in Bandung City based on the Technical Guidelines for Pharmaceutical Service Standards in accordance with the Regulation of the Minister of Health No. 73 of 2016. Method: The method used was descriptive observational with a prospective approach through direct observation, interviews, and documentation. Evaluation was conducted on both technical and administrative parameters in the receiving and storage of pharmaceutical preparations. Results: The study showed that the drug receiving system achieved a compliance rate of 85.7%, and the drug storage system achieved 94.44%, both categorized as “Excellent.” Pharmacy X has properly implemented procedures for physical verification, invoice data matching, expiration date and batch number checks. Additionally, drug storage follows the FIFO and FEFO principles, grouping based on dosage forms, and monitoring of room and refrigerator temperatures. The use of an electronic recording system further enhances stock management accuracy and efficiency. This pharmacy has demonstrated compliance with established standards and implemented patient safety principles in pharmaceutical management. These findings indicate that Pharmacy X can serve as a model for professional and high-quality pharmaceutical practice. Conclusion: The implementation of pharmaceutical service standards has been proven to improve service quality and the efficiency of drug distribution systems at the community pharmacy level.